Metabolism of Amino Acids in Cancer - Wei, Zhen; Liu, Xiaoyi; Cheng, Chunming; Yu, Wei; Yi, Ping (Frontiers in Cell and Developmental Biology, 2021)
Genetic mutation-driven metabolic reprogramming has been widely recognized as a hallmark of malignancy. Uptake and metabolism of amino acids are aberrantly upregulated in many cancers that display particular amino acid addiction. Amino acids facilitate cancer cells to survive and proliferate under genotoxic, oxidative, and nutritional stress through their extremely extensive effects. And thus targeting amino acid metabolism is becoming the potential therapeutic strategy for cancer patients. In this review, we will systematically summarize recent progress of amino acid metabolism in malignancy, and discuss their interconnection with mTORC1 signal, epigenetic modification, tumour growth and immunity, and ferroptosis. Finally, we will highlight the potential therapeutic applications.